Switching From Immediate-Release to Fractionated Dual-Release Hydrocortisone May Improve Metabolic Control and QoL in Selected Primary Adrenal Insufficiency Patients - Delle Cese, Francesca; Corsello, Andrea; Cintoni, Marco; Locantore, Pietro; Pontecorvi, Alfredo; Corsello, Salvatore Maria; Paragliola, Rosa Maria (Frontiers in Endocrinology, 2021)
Objective: The use of once-daily dual-release HC (DR-HC) in primary adrenal insufficiency (PAI) is often associated with benefits in metabolic parameters when compared to immediate-release HC (IR-HC). In this study, we evaluated the effects on clinical, biochemical and metabolic parameters of switching from IR-HC to lower-dose DR-HC given both in once and fractionated daily doses. Methods: Twenty autoimmune-PAI subjects were included. Patients on thrice-daily 30 mg IR-HC regimen (group A) were switched to DR-HC 25 mg/day given in two daily doses (20 mg in the morning and 5 mg at 2.00 p.m.); patients on twice-daily 25 mg IR-HC regimen (group B) were switched to DR-HC 20 mg once daily. Biochemical and metabolic parameters, BMI and quality of life (QoL) were evaluated at the baseline and six months after the switch. Results: After the switch to DR-HC, a significant decrease in adrenocorticotropic hormone (ACTH), HbA1c, total cholesterol, triglycerides, LDL, cholesterol, BMI as well as a significant improvement in QoL, was observed in both groups. At 6 months, ACTH levels were lower in group A. Conclusion: The DR-HC is a valid and effective therapeutic strategy useful to improve the metabolic control and the QoL in PAI. The reduction of ACTH levels with DR-HC regimens reflects a better biochemical control of PAI, obtained by using a lower and more physiological HC formulation. Both once-daily and fractionated daily doses of DR-HC showed advantages compared with IR-HC formulation.